Answer:
x = -1/2 , y = -1
Explanation:
Solve the following system:
{y = 4 x + 1 | (equation 1)
{y = 2 x | (equation 2)
Express the system in standard form:
{-(4 x) + y = 1 | (equation 1)
{-(2 x) + y = 0 | (equation 2)
Subtract 1/2 × (equation 1) from equation 2:
{-(4 x) + y = 1 | (equation 1)
{0 x+y/2 = (-1)/2 | (equation 2)
Multiply equation 2 by 2:
{-(4 x) + y = 1 | (equation 1)
{0 x+y = -1 | (equation 2)
Subtract equation 2 from equation 1:
{-(4 x)+0 y = 2 | (equation 1)
{0 x+y = -1 | (equation 2)
Divide equation 1 by -4:
{x+0 y = (-1)/2 | (equation 1)
{0 x+y = -1 | (equation 2)
Collect results:
Answer: {x = -1/2 , y = -1